Passion simple and Madame, c'est à vous que j'écris: "That's MY Desire" - Elizabeth Richardson Viti (Studies in 20th & 21st Century Literature, 2001)
No two texts better exemplify the contemporary "he said, she said" phenomenon than Annie Ernaux's Passion simple and Alain Gérard's Madame, c'est à vous que j'écris. Ernaux's book, published in 1991, recounts the author's heretofore hidden affair with a foreign businessman living temporarily in France, and Gérard's, published four years later, is an explicit response in which the writer, dissatisfied with Ernaux's account, assumes the lover's identity and chronicles events from his perspective. The result is a literary "tac à tac" very much in the public eye in which a man and woman both wish to tell their side of the story about a past sexual relationship. For her part, Ernaux gives primacy to woman as sexual subject and describes an erotic economy where the lover is nothing more than simple support for the female imaginary. Gérard responds to Ernaux's reduction of the lover to pure sex object by reestablishing his primacy as well as that of the phallus, around which desire has traditionally revolved. Indeed, what is most intriguing about this unusual pair is their disagreement over the definition of desire, and thus, how they illustrate the fundamental feminist notion that gender informs writing as well as reading.
Keywords: Annie Ernaux; Passion simple; Simple Passion; Alain Gerard; Madame c' est à vous que j' écris; tac au tac; desire; feminism; femeist; gender